2012
DOI: 10.1111/j.1474-9726.2012.00792.x
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of age‐related oxidative stress prevents hippocampal synaptic plasticity deficits by protecting d‐serine‐dependent NMDA receptor activation

Abstract: SummaryOxidative stress (OS) resulting from an imbalance between antioxidant defenses and the intracellular accumulation of reactive oxygen species (ROS) contributes to age-related memory deficits. While impaired synaptic plasticity in neuronal networks is thought to underlie cognitive deficits during aging, whether this process is targeted by OS and what the mechanisms involved are still remain open questions. In this study, we investigated the age-related effects of the reducing agent N-acetyl-L-cysteine (L-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 48 publications
5
88
0
Order By: Relevance
“…Further studies will have to show whether Nrf2 has a direct effect on Srr gene expression. The first evidence for this might come from the observation that serine racemase expression is regulated by oxidative stress (29). Although Nrf2 activation has not been directly associated with eNOS signaling, two genes (Fifg and Prkaa2) of this canonical pathway that were regulated by RA839 are regulated by Nrf2 and protect against oxidative stress, respectively (30 -32).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies will have to show whether Nrf2 has a direct effect on Srr gene expression. The first evidence for this might come from the observation that serine racemase expression is regulated by oxidative stress (29). Although Nrf2 activation has not been directly associated with eNOS signaling, two genes (Fifg and Prkaa2) of this canonical pathway that were regulated by RA839 are regulated by Nrf2 and protect against oxidative stress, respectively (30 -32).…”
Section: Discussionmentioning
confidence: 99%
“…Not surprising therefore that anti-oxidants were intensively tested as potential therapeutic agents against the negative consequences of brain ageing and neurodegenerative disorders [84][85][86]. Generally, it was found that anti-oxidant treatment or activation of anti-oxidative pathways improve brain functions and partially restores age-dependent changes in gene expression both in normal ageing [87,88] and in models of accelerated ageing [89,90]. Clinical data suggest that dietary anti-oxidants have some protective effects against AD, Parkinson's disease and amyotrophic lateral sclerosis [91] and also in pharmacological and genetic models of neurodegenerative disorders [92][93][94].…”
Section: Processes Contributing To Brain Ageingmentioning
confidence: 99%
“…And, oxidative stress-initiated neuroendocrine alterations within the amygdala, including amygdalar hyperactivity and dendritic shrinking (Wellman, 2001;Vyas et al, 2002;Kreibich and Blendy 2004;Brown et al, 2005;Radley et al, 2006;Wood et al, 2010), can further potentiate synaptic disturbances by disrupting the hippocampus-amygdala projections. Furthermore, free radicals are known to oxidize the extracellular sites of glutamatergic N-methyl-D-aspartate receptors, leading to attenuation of LTP and synaptic neurotransmission (Haxaire et al, 2012;Lee et al, 2012;Rai et al, 2013). Collectively, these events offer an attractive explanation for oxidative stress-induced behavioral and cognitive impairment.…”
Section: Oxidative Stress and The Brainmentioning
confidence: 99%